LEARNING FROM NATURE: FOSTERING ENVIRONMENTAL AWARENESS IN ISLAMIC NATURE-BASED ELEMENTARY SCHOOL - Ma’as Shobirin; Muhammad Fauzan Muttaqin; Fatkhul Arifin; Abu Choir (PD PGMI se Indonesia, 2026)
This study examines the application of experiential learning through a learning from nature approach in fostering students' environmental awareness at MI Alam Alfa Kids, an Islamic nature-based elementary school in Pati, Central Java, Indonesia. Employing a qualitative case study design, data were collected over one academic semester through systematic non-participant observations, semi-structured interviews with three classroom teachers, one school principal, and eight students, alongside documentation analysis. Data were analyzed using reflexive thematic analysis following Braun and Clarke (2006, 2019). Findings reveal three interconnected results. First, nature-based experiential learning was implemented through seven systematic activity forms including gardening, zero-waste programs, project-based learning, and outing classes embedded in daily instructional routines. Second, these activities fostered environmental awareness across cognitive, affective, and behavioral dimensions, with students demonstrating experience-based ecological knowledge, faith-embedded moral responsibility, and self-initiated pro-environmental behavior including peer social agency. Third, teacher facilitation, consistent role modeling, and an institutionally coherent school culture functioned as mutually reinforcing mechanisms sustaining environment-oriented learning. This study introduces the concept of faith-integrated experiential learning as a theoretically distinct pedagogical model in which Islamic values of stewardship (khalifah) and natural balance (mizan) amplify and sustain environmental commitment beyond outcomes documented in secular educational contexts.